Clonal Expansion of Mitochondrial DNA Deletions and the Progression of Multiple Sclerosis - R. Campbell, Graham; J. Mahad, Don (CNS & Neurological Disorders - Drug Targets, 2012)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS). Mechanisms of disease progression in MS are poorly understood but are thought to relate to both focal pathology as well as diffuse inflammation in the white and grey matter. Evidence points to neurodegeneration combined with a loss of cellular function in the remaining tissue as an important factor to the progression of MS. Mitochondria are implicated to play a role in the pathogenesis of MS with evidence of loss of mitochondrial respiratory chain activity, down regulation of both nuclear DNA and mitochondrial DNA (mtDNA) encoded transcripts as well as oxidative damage to, and deletions of, the mitochondrial DNA (mtDNA). The double stranded circle of mtDNA (16.6 kb) encompasses genes encoding key subunits within the mitochondrial respiratory chain required for the production of ATP as well as transfer RNA and ribosomal RNA molecules within the cell. The stability of mtDNA is essential for a healthy CNS as highlighted by the patients with primary mitochondrial disease. In this review, we focus on the potential role of mtDNA mutations, in particular somatic mtDNA deletions, in the pathogenesis of the progressive stage of MS. We propose clonal expansion of somatic mtDNA deletions as a potential molecular link between early inflammatory events and a delayed cellular energy failure, dysfunction and degeneration. The high level of somatic mtDNA deletions within single cells in MS is likely to cause cellular dysfunction as well as increase the susceptibility of the CNS tissue to additional stress.
Keywords: Adenosine triphosphate